Antibacterial activity of new ciprofloxacin conjugates - Gheith M Alasadi; Zaid Al-Obaidi (College of Pharmacy / Mustansiriyah University, 2024)
Numerous antibiotics are no longer effective against certain germs, rendering it harder to treat illnesses and inflicting unnecessary suffering and death on many individuals. This necessitates the introduction of new antibacterial agents to counteract bacterial antibiotic resistance. In a previous published work, new ciprofloxacin conjugates were synthesized by amidification and esterification of the ciprofloxacin core structure. The antibacterial activity of these new ciprofloxacin derivatives was evaluated by clinical and laboratory standard instruments. The Laboratory of Public Health/ Branch of Microbiology in Karbala evaluated their collected strains for each species. All compounds exhibited antibacterial properties, where the inhibition zones were measured and the values reported. Bacterial susceptibility to recently produced chemicals tended to be as follows: Pseudomonas aeruginosa is followed by Klebsiella pneumoniae, Proteus mirabilis, and Escherichia coli. The synthesized compounds had stronger antibacterial properties than the ciprofloxacin used as a starting point.